PENGARUH FINANCIAL SLACK, FREE CASH FLOW, DAN FIRM SIZE TERHADAP CSR EXPENDITURE DENGAN LEVERAGE SEBAGAI MODERASI : (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2021-2025) - Irma Lusiana; Dien Noviany Rahmatika; Teguh Budi Raharjo (Jurnal Maneksi, 2026)
Introduction: CSR Expenditure is a concrete indicator of acompany‘s commitment to social responsibility, yet the extent of such expenditure remains shaped by internal financial conditions that have received limited empirical attention in Indonesia's food and beverage manufacturing sector. This study examines the effect of Financial Slack, Free Cash Flow, and Firm Size on CSR Expenditure, and the moderating role of Leverage.Methods: “A descriptive quantitative approach was applied using secondary data from annual reports and sustainability reports of food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2021-2025 period. Through purposive sampling, 43 companies met the criteria and were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) after classical assumption testing with SPSS version 22” Results: “The results indicate that financial slack has a negative but insignificant effect, while free cash flow has a positive but insignificant effect on CSR expenditure. In contrast, firm size has a positive and significant effect on CSR expenditure. Leverage is found to strengthen the negative effect of financial slack, does not moderate the effect of free cash flow, and weakens the positive effect of firm size on CSR expenditure. These findings provide important insights that CSR allocation decisions in food and beverage manufacturing companies are more strongly determined by firm scale and capital structure than by the availability of short-term financial resources alone.” Keywords: CSR Expenditure, Financial Slack, Firm Size, Free Cash Flow, Leverage